2020
DOI: 10.1088/1361-6463/abc4aa
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of dynamics of a single spark-induced bubble in saline water

Abstract: We investigated the behavior of single bubbles generated by spark discharge under different electric fields and water properties. A higher discharge energy is known to generate a larger bubble. However, our results show that the hydraulic efficiency decreases with increasing charging voltage, but increases with increasing charging capacitance. We found that the water conductivity has little influence on the bubble behavior, whereas a higher water temperature generates a larger bubble with higher hydraulic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Apart from the geometric parameters (i.e., r¯$\bar{r}$ and φ ) marked in the images, the normalized width (w¯$\bar{w}$) and the joint angle ( θ ) are fixed as w¯$\bar{w}$ = 0.04 and θ = 180°, respectively. h) Ashby plot of tensile strength ( σ b ) versus stretchability ( ε b ) for existing SNMs, [ 45,49–51,55 ] typical soft materials (e.g., polydimethylsiloxane (PDMS), [ 59 ] liquid crystal elastomer (LCE), [ 60 ] semi‐interpenetrating polymer network (SIPN) hydrogel, [ 61 ] double network (DN) hydrogel [ 34 ] ), and HSNMs proposed in the current work. Scale bars, 10 mm in (g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the geometric parameters (i.e., r¯$\bar{r}$ and φ ) marked in the images, the normalized width (w¯$\bar{w}$) and the joint angle ( θ ) are fixed as w¯$\bar{w}$ = 0.04 and θ = 180°, respectively. h) Ashby plot of tensile strength ( σ b ) versus stretchability ( ε b ) for existing SNMs, [ 45,49–51,55 ] typical soft materials (e.g., polydimethylsiloxane (PDMS), [ 59 ] liquid crystal elastomer (LCE), [ 60 ] semi‐interpenetrating polymer network (SIPN) hydrogel, [ 61 ] double network (DN) hydrogel [ 34 ] ), and HSNMs proposed in the current work. Scale bars, 10 mm in (g).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1h presents an Ashby plot that characterizes stretchability ( ε b ) and tensile strength ( σ b ) of the proposed HSNMs and some other representative soft materials reported previously in the literatures, including the existing SNMs, [ 45,49–51,55 ] polydimethylsiloxane (PDMS), [ 59 ] liquid crystal elastomers (LCEs), [ 60 ] semi‐interpenetrating polymer network (SIPN) hydrogels, [ 61 ] and typical double network (DN) hydrogels. [ 34 ] It is observed that the HSNMs proposed in this work provide a considerably larger σ b ‐ ε b space than these typical soft materials.…”
Section: Resultsmentioning
confidence: 99%
“…An important trend in the development of flexible electronic devices involves the evolution of planar arrangements of solid‐state elements [ 1–3 ] into 3D format, [ 4–11 ] which are of growing interest for a variety of emerging applications, ranging from micro‐/nano‐electromechanical systems (MEMS/NEMS), [ 12–15 ] biomimetic devices, [ 5,16–19 ] to energy harvesters, [ 20–23 ] micro‐robotics, [ 24–27 ] and to bio‐integrated electronics. [ 28–33 ] Various approaches have been established to manufacture flexible electronics with arbitrarily designed 3D geometries across different length scales (e.g., from submicron to a few centimeters).…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the great efforts made by the researchers across the world, flexible pressure sensors have experienced a great evolution, [ 36–45 ] with improved performances including sensitivity, limit of detection (LOD), response speed, etc., [ 46–53 ] based on the enhancement of materials, [ 54–63 ] fabrication methods, [ 64–72 ] microstructure designs [ 73–81 ] and different working mechanisms, [ 82–90 ] enabling a variety of applications of flexible electronic field [ 14,91–96 ] (Figure 1). The progress of microstructural flexible pressure sensors in recent years is summarized in this review.…”
Section: Introductionmentioning
confidence: 99%